Synthesis and Mössbauer characterization of Cu and Cr doped magnetites (2003)
A detailed Móssbauer investigation of magnetites prepared under different hydrothermal conditions and doped with Cu and Cr is presented. The samples were characterized by means of room temperature Móssbauer spectrometry, infrared spectroscopy, and X-ray diffraction. Móssbauer results show that the hydrothermal method produces highy stoichiometric and relativelly well-crystallized magnetites. The results suggest that the best samples are obtained when the alkaline solution is added quickly to the ferrous solution. It was also found that mixing the solutions under constant ultrasonic stirring produce magnetites with slightly better crystallinity and stoichiometry than the samples produced under magnetic or nitrogen bubbling stirring. The effect of the Cu and Cr on the hyperfine parameters is also presented and discussed.